The biological dimensions of transcendent states: A randomized controlled trial - Church, Dawson; Yang, Amy; Fannin, Jeffrey; Blickheuser, Katharina (Frontiers in Psychology, 2022)
This study evaluated the biological dimension of meditation and self-transcendent states. A convenience sample of 513 participants were drawn from attendees at a four-day guided meditation workshop. Half the participants received an active Control intervention; all were assessed on a variety of measures: biological (salivary immunoglobulin-A (SIgA), cortisol, qEEG (N = 117, subset of Experimental group)), psychological (anxiety, pain, posttraumatic stress disorder (PTSD), positive emotions, transcendent states), and physiological (physical functioning). No significant difference in psychological symptoms or positive emotions was observed between Experimental and placebo groups at baseline. At post-test, significant improvements were noted in the Experimental group: 49.5% median increase in SIgA (p = 0.01); qEEG z-score analysis identified sustained stress reduction, including delta frequency band amplitude increases, high beta decreases, and faster acquisition of sustained alpha states (all p <0.001). Psychological symptoms also improved on all measures. At 6-month follow-up (N = 140), PTSD and somatic symptoms significantly improved from baseline, and post-test versus 6-month follow-up results indicated significant increases in happiness and spiritual and physical oneness and decreases in depressive symptoms. Findings suggest that autonomic self-regulation and transcendent states may be measured in both biological and psychological dimensions and are associated with pervasive health benefits.